Nursing in the face of climate change, a bioethical commitment - Segura Miñope, Sussan Giovana (2022)
Given the dizzying and unsustainable progress that comes with the degradation of natural habitat and as a consequence the cause of environmental diseases that put at risk the health and integrity of the person. The present work was developed through a bibliographic review, around the nursing bioethical commitment to climate change and its implication in the health of the person. Included in current national and international regulations on ethics and deontology, which emphasize their responsibility in this area through surveillance and prevention. This response to climate change is developed in all areas of action such as healthcare, teaching, management and administration and research. The nursing care of the person, the community and the environment aims to improve the quality of life of people; having as a basis the personalistic bioethics that enriches, enhances and perfects care by defending the physical life of the person, without which its existence would not be possible.